Celestial Delights The Best Astronomical Events Through 2020 - Reddy, Francis (The Patrick Moore Practical Astronomy Series, 2012)
Celestial Delights is the essential 'TV Guide' for the sky. Through extensive graphics integrated with an eight-year-long calendar of sky events, it provides a look at "don't miss" sky events, mostly for naked-eye and binocular observing. It is organized by ease of observation - lunar phases and the brighter planets come first, with solar eclipses, the aurora, and comets coming later. This third edition also includes a hefty dose of sky lore, astronomical history, and clear overviews of current science. It provides a handy reference to upcoming naked-eye events, with information broken out in clear and simple diagrams and tables that are cross-referenced against a detailed almanac for each year covered. This book puts a variety of information all in one place, presents it in a friendly way that does not require prior in-depth astronomical knowledge, and provides the context and historical background for understanding events that astronomy software or web sites lack.